Energy analysis of a solar driven vaccine refrigerator using environment-friendly refrigerants for off-grid locations. (September 2021) - Raihan Uddin, Mohammed; Mahmud, Shadman; Salehin, Sayedus; Abdul Aziz Bhuiyan, Md; Riaz, Fahid; Modi, Anish; Salman, Chaudhary Awais
Highlights: A modelling framework for performance evaluation of a solar PV vaccine refrigerator is presented. Three environment-friendly refrigerants R152a, R1234yf, and R1234ze(E) have been investigated as possible replacements for the commonly used R134a. R152a has been found to be the best performing refrigerant. Techno-economic optimization of the energy systems consisting of solar PV and battery has been performed using HOMER software. Case studies for two remote, off-grid localities in Bangladesh and South Sudan have been presented. Abstract: In many remote localities, one of the underlying reasons for not receiving life-saving vaccines is the lack of electricity to store the vaccines in the required refrigerated conditions. Solar Photovoltaic (PV) refrigerators have been considered as a viable and green solution to store the vaccines in remote localities having no access to electricity. In this paper, a detailed methodology has been presented for the performance evaluation of a solar PV powered vaccine refrigerator for remote locations. Thermal modelling with hourly cooling load calculations and refrigeration cycle simulations were carried out. The performance parameters for three environment-friendly refrigerants: R152a, R1234yf, and R1234ze(E) has been compared against the commonly used R134a for two remote, off-grid locations in Bangladesh and South Sudan. The energy systems comprising of solar PV panels and batteries to run the refrigerator were modelled in HOMER software for techno-economic optimizations. For both the locations, R152a was found to be the best performing refrigerant exhibiting higher COP (2%−5.29%) as compared to the other refrigerants throughout the year, while R1234ze(E) exhibited COPs on par with R134a, and R1234yf had the least performance. Techno-economic analysis showed an energy system providing electricity to the refrigerator with R152a also had lower levelized cost of electricity (0.48%−2.54%) than the systems having other refrigerants in these locations.